Consumption trends in the UK, 1975 - 99 - Laura Blow; Andrew Leicester; Zoë Oldfield (Institute for Fiscal Studies (IFS), 2004)
How and why has the way in which the average British family spends its money changed over the past 25 years? Those are the key questions examined in this report, using data from the UK FES between 1975 and 1999. It looks not only at broad changes in total spending, but also at how the division of expenditure between basics and non-basics and between durable goods, non-durable goods and services has altered over time.
Keywords: 330